2020
DOI: 10.1123/jpah.2019-0441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Total and Domain-Specific Physical Activity and Associated Factors Among Nepalese Adults: A Quantile Regression Analysis

Abstract: Aim: To analyze the data from the World Health Organization Nepal STEPS survey 2013 to determine the prevalence of total and domain-specific physical activity (PA) and associated factors among Nepalese adults. Methods: A multistage cluster sampling technique was used to proportionately select participants from the 3 ecological zones (Mountain, Hill, and Terai) in Nepal. The Global PA Questionnaire was used to assess PA. The data were analyzed using quantile and ordinary least square regression. Results: Only 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Participation in LTPA was minimal, and gender variations were evident, with men more likely to engage in LTPA. These findings support previous quantitative studies from Nepal, including the most recent World Health Organization Stepwise Approach to Surveillance (STEPS) survey [ 12 , 14 , 23 , 35 , 36 ]. Gender differences were also reported for walking, with men walking more regularly and allocating more time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Participation in LTPA was minimal, and gender variations were evident, with men more likely to engage in LTPA. These findings support previous quantitative studies from Nepal, including the most recent World Health Organization Stepwise Approach to Surveillance (STEPS) survey [ 12 , 14 , 23 , 35 , 36 ]. Gender differences were also reported for walking, with men walking more regularly and allocating more time.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other South Asian countries [ 13 ], occupational and transport-related activities are the most prevalent forms of physical activity (PA) while engagement in LTPA is minimal [ 12 ]. Overall, the percentage contribution of LTPA to total PA was 1% among males and 0.3% among females aged 40 years and older [ 14 ]. The retired or unemployed, those with higher education and those from affluent households were most likely to engage in LTPA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among participants, PA was mostly the result of routine activities or because there was no other alternative. Consistent with a previous Nepalese study (Kadariya & Aro, 2018; Paudel et al, 2020), women were primarily involved in household activities, whereas active commuting was the dominant form of PA for men. However, women with chronic diseases participated more frequently in other nondomestic forms of PA compared with those without these diseases.…”
Section: Discussionsupporting
confidence: 88%
“…14 Previous Nepalese studies have reported an age-related decline in active-commuting and negative association with higher education, marital status and unpaid employment. 15 …”
Section: Introductionmentioning
confidence: 99%